PENGARUH infrastruktur dan investasi swasta terhadap pertumbuhan ekonomi kabupaten / kota di kalimantan timur (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2020)
The purpose of this research was determine the effect of infrastructure and private investment to economic growth districts / cities in East Kalimantan Province. The data used are panel data with the period from 2009 to 2018 for 9 in districts / cites in East Kalimantan Province. To find the results of the BLUE (Best Linear Unbiased Estimator), the test for a panel like Chow Test, Haussman Test and Lagrange Test so that got common effect panel data model for the complete data with characteristics as above. The data is processed using EViews (Econometric Views) computer program version 10.0. The results indicate that (1) health infrastructure, education infrastructure and private investment variables have significant effect to the regional economic growth. (2) road infrastructure and electricity infrastructure variables have not significant effect to the regional economic growth.